The Notion of 'Singularity' in the Work of Gilles Deleuze. Issue 1 (February 2017) - Borum, Peter
Abstract : In Deleuze, singularity replaces generality in the economy of thought. A Deleuzian singularity is an event, but the notion comprises the effectuation of the event into form. The triptych émission–distribution–répartition itself distributes the dimensions of the passage from form-giving event to topological morphology. The Deleuzian concept of intensity allows thinking both pre-individuality and the rhizomatic connection of singularities on the metaphysical surface of structure. Reflections upon the philosophy of differential calculus allow for a coherent scaffolding reaching from pre-individual intensity to specific individuality, in the passage from transcendental genesis to empirical morphogenesis. But if singularity as event is intensive, singularity as determinant of morphology – and hence, of structural metastability – is not. Although the differential scaffolding covers both intensive difference and extensive equality, and so the two sides of the notion of singularity, the concept of intensity remains slightly displaced, rendering conceptually difficult not only the perception of intensity, but also the contemplation of individual duration, if viewed in the terms of genetic 'indi-drama-differen t/c iation'. The essay concludes that it is art that may let us consciously contemplate our pre-individual differences.